2012
DOI: 10.1152/ajpheart.01042.2011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heart rate on hemodynamic endpoints under concomitant microvascular disease in a porcine model

Abstract: Diagnosis of the ischemic power of epicardial stenosis with concomitant microvascular disease (MVD) is challenging during coronary interventions, especially under variable hemodynamic factors like heart rate (HR). The goal of this study is to assess the influence of variable HR and percent area stenosis (%AS) in the presence of MVD on pressure drop coefficient (CDP; ratio of transstenotic pressure drop to the distal dynamic pressure) and lesion flow coefficient (LFC; ratio of %AS to the CDP at the throat regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…In our recent preclinical trials we have found that CDP is a promising clinical diagnostic parameter that can independently assess the severity of epicardial stenosis and microvascular impairment . Further, it was also reported in our recent studies that CDP is independent of variable hemodynamic conditions such as heart rate and contractility under both epicardial and microvascular impairment .…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In our recent preclinical trials we have found that CDP is a promising clinical diagnostic parameter that can independently assess the severity of epicardial stenosis and microvascular impairment . Further, it was also reported in our recent studies that CDP is independent of variable hemodynamic conditions such as heart rate and contractility under both epicardial and microvascular impairment .…”
Section: Discussionsupporting
confidence: 79%
“…We have recently proposed and tested CDP, a nondimensional diagnostic parameter formulated based on fundamental fluid dynamic principles as a measure of stenosis severity in an animal model . CDP, by definition, combines both hyperemic pressure drop and velocity measurements.…”
Section: Discussionmentioning
confidence: 99%
“…CDP is defined as the ratio of the trans-stenotic pressure drop to the dynamic pressure proximal to a stenosis [22]. Simultaneous measurements of functional parameters (pressure drop and proximal velocity), necessary for the evaluation of CDP, can be readily obtained during routine cardiac catheterization procedures using a dual-sensor tipped guidewire, also known as a combowire [23][24][25][26][27]. CDP has been validated in pre-clinical trials [21,23,24,26,27] and under a clinical setting [25], in order to delineate epicardial stenoses.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneous measurements of functional parameters (pressure drop and proximal velocity), necessary for the evaluation of CDP, can be readily obtained during routine cardiac catheterization procedures using a dual-sensor tipped guidewire, also known as a combowire [23][24][25][26][27]. CDP has been validated in pre-clinical trials [21,23,24,26,27] and under a clinical setting [25], in order to delineate epicardial stenoses. Furthermore, it has been shown to be independent of heart rate [24,26] and contractility [27,28] in recently conducted in vivo animal studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation